Use of Value Stream Mapping in a Case Study in Basement Construction - Espinoza, Lisseth R. (2021)
The Value Stream Mapping (VSM) as a management tool helps evaluate the waste within the workflow. However, it must be adapted to the construction since it was originated in manufacture. This adaptation is possible through appropriate process mapping. This study aims to map the process of the basement construction system in the execution of a building in Lima-Peru city. The building in the case study will have nine basements and 11-floor levels. An adaptation of the optimization cycle for construction projects was used. It allows mapping all the relevant activities and proposing and implementing improvements in the construction system. As a result, three maps were obtained. The first one is a map of the current state (VSM 1). The second one is a map of the current state with improvements (VSM 2). Finally, a third map of the future state with improvements (VSM 3). This study demonstrated that it is possible to adapt the VSM in basement construction and the usefulness of this tool to evaluate and reduce waste within the workflow.